Kemampuan representasi matematis siswa pada materi kesebangunan dan kekongruenan di kampung sukawening - Suci Marliani; Nitta Puspitasari (Institut Pendidikan Indonesia, 2022)
The ability to mathematical representation is an important aspect that must be learned and mastered by students. The knowledge of mathematical representation helps students in the understanding of concepts, problem-solving, mathematical communication, mathematical connection, and the application of mathematical ideas through modeling. The purpose of this study is to determine the ability of students’ mathematical representation in similar and congruent materials. The type of research used was in the form of descriptive qualitative with the research subjects of four students of junior high school class IX in Sukawening Village. Data collection techniques used include tests, interviews, and documentation. The data analysis techniques used are in the form of data reduction, data presentation, and drawing conclusions. The results showed that students' mathematical representation ability is moderate. The average score obtained from the three measured indicators was 44.8%. The highest score is found in the verbal indicator, which is 50%, followed by the image indicator at 42.5%, and the symbol indicator at 40.62%. Problems faced by students in answering the measured indicators, including low understanding and mastery of mathematical concepts and students' errors in understanding the material. This results in students not being able to represent their mathematical ideas and ideas in the ordered form. Kemampuan representasi matematis merupakan aspek penting yang harus dipelajari dan dikuasai oleh siswa. Kemampuan representasi matematis membantu siswa dalam dalam pemahaman konsep, penyelesaian masalah, komunikasi matematis, koneksi matematis, dan penerapan ide matematis melalui pemodelan. Tujuan penelitian ini adalah mengetahui kemampuan representasi matematis siswa pada materi kesebangunan dan kekongruenan. Jenis penelitian yang digunakan berupa kualitatif deskriptif dengan subjek penelitian empat orang siswa SMP kelas IX yang berada di Kampung Sukawening. Teknik pengumpulan data yang digunakan diantaranya tes, wawancara, dan dokumentasi. Teknik analisis data yang digunakan berupa reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kemampuan representasi matematis siswa ada pada kategori sedang. Rata-rata skor yang diperoleh dari ketiga indikator yang diukur sebesar 44,8%. Skor tertinggi terdapat pada indikator verbal, yakni 50%, diikuti oleh indikator gambar sebesar 42,5%, dan indikator simbol sebesar 40,62%. Permasalahan yang dihadapi oleh siswa dalam menjawab indikator yang diukur, diantaranya rendahnya pemahaman dan penguasaan konsep matematis dan kesalahan siswa dalam memahami materi. Hal tersebut mengakibatkan siswa belum mampu merepresentasikan ide dan gagasan matematisnya ke dalam bentuk yang diperintahkan.